(untitled) (International journal of medical sciences, 2026)
This article analyzes the current state of the training process for obstetrician-gynecologists, competency-based approaches in medical education, and the implementation of simulation technologies. According to the research findings, the use of innovative teaching methods in developing practical skills significantly increases the level of professional preparedness of specialists. The obtained results contribute to improving the quality of training obstetrician-gynecologist personnel in higher medical educational institutions.